PERANCANGAN SISTEM KONTROL ASAP ROKOK PADA RUANG MEROKOK MENGGUNAKAN METODE FUZZY - Muchammad Zufar Badubah; Mochammad Rusli; Erni Yudaningtyas (Jurnal Mahasiswa TEUB, 2023)
Cigarettes are a mixture of tobacco, cloves and other ingredients wrapped in paper. The content of substances in cigarettes consists of nicotine, carbon monoxide (CO), tar which are carcinogenic and free radicals, such as nitric oxide radicals and so on. However, this application is limited only by measuring gases which are considered to represent the overall content of cigarette smoke. The gas is Hydrogen and Ethanol. In this study smoke and CO gas levels will be used as input to the control system, the output is in the form of a pwm duty cycle. The input value will be processed by fuzzification, the fuzzy set value will be matched with the rule value used, then it will be the output value after going through the defuzzification process. Fuzzy Logic Controller to get the PWM value from the relay which will be used to adjust the exhaust fan rotating speed. The test results show that fuzzy logic can provide a rule based on the existing smoke sensor in the smoke detector. Based on the test results obtained, that fuzzy logic can be implemented as a rule maker in the detection tool as soon as possible. So it can be concluded that the detection tool as soon as possible can carry out their respective tasks properly. Keywords : cigarette smoke control system, fuzzy method, nicotine, carbon monoxide